Connective tissue grafts in conjunction with implants installed immediately into extraction sockets. An experimental study in dogs - Caneva, Marco [UNESP]; Botticelli, Daniele [UNESP]; Viganò, Paolo; Morelli, Fabrizio; Rea, Massimiliano; Lang, Niklaus P. (Wiley, 2013)
Aim: To evaluate the influence of a sub-epithelial connective tissue graft placed at the buccal aspect of implants installed immediately after tooth extraction on the dimensional changes of hard and soft tissues. Materials and Methods: In six Labrador dogs a bilateral partial- thickness dissection was made buccal to the second mandibular premolar. At the lingual aspect, full-thickness flaps were elevated. The teeth were extracted and implants installed immediately into the distal socket. A connective tissue graft was obtained from the palate and applied to the buccal aspect of the test sites, whereas contra-laterally, no graft was applied. The flaps were sutured to allow a non-submerged installation. After 4 months of healing, the animals were sacrificed, ground sections were obtained and histomorphometric analyses were performed. Results: After 4 months of healing, all implants were integrated (n = 6). Both at the test and at the control sites bone resorption occurred: 1.6 mm and 2.1 mm, respectively. The difference was not statistically significant. The coronal aspect of the peri-implant soft tissue was wider and located more coronally at the test compared with the control sites. The differences were statistically significant. Conclusions: The application of a connective tissue graft placed at the buccal aspect of the bony wall at implants installed immediately after tooth extraction yielded a minimal preservation of the hard tissues. The peri-implant mucosa, however, was significantly thicker and more coronally positioned at the test compared with the control sites. © 2012 John Wiley & Sons A/S.
Keywords: Alveolar bone preservation; Animal study; Connective tissue; Extraction socket; Graft; Implant dentistry; Regeneration